Probiotification and its effects on antioxidant properties of herbal teas - Ibrahim, Nur Athirah (2014)
This study investigated the antioxidant properties of freshly prepared and lactic fermented herbal teas. Herbal teas were known to have powerful antioxidant properties. There has been an increased interest in the exploration of enhancing the effectiveness of naturally occurring antioxidant. Brewing time which could affect the nutritive values of teas are often neglected and ignored. Reports on the effect of lactic fermentation on antioxidant properties of herbal teas are limited. Furthermore, many probiotic drinks available in the market are dairy-based. This represents inconvenience for consumers who are on low cholesterol diet and lactose intolerant. Hence, the objectives of this study were to examine the effect of brewing time on the yield of phenolic contents of herbal teas, to determine the suitability of herbal teas as raw materials for the production of probiotic herbal teas and to study the effect of lactic fermentation on antioxidant properties of herbal teas. Four local commercial herbal teas namely “Allspice”, “Scaphium”, “Gora”, and “Cinnamon” were purchased from the local store to be subjected to lactic fermentation. The bacteria used was Lactobacillus casei Shirota strain. The antioxidant capacity of freshly prepared and lactic fermented herbal teas was measured using three different assays namely DPPH assay, FRAP assay, and βeta-carotene linoleate bleaching assay. Phenolic contents (TPC) was analyzed using Folin-Ciocalteu reagent and flavonoid contents (TFC) was measured using the aluminium chloride method. The probiotic herbal teas were inoculated with 24 h-old lactic culture and incubated at 37 °C overnight. Changes in pH, acidity, sugar content, and viable cell counts during fermentation under controlled conditions were monitored. It was observed that herbal teas brewed for 3 min yielded the highest phenolic contents. Lactobacillus casei retained its viability in all herbal teas after 24 hour of fermentation. Majority of pH and total sugar of probiotic herbal teas were significantly reduced (p< 0.05) while total acidity of probiotic herbal teas were significantly increased (p< 0.05) with fermentation. TPC and TFC of probiotic herbal teas were significantly higher (p< 0.05) than the freshly prepared herbal teas. The antioxidant activity of fermented herbal teas were higher than freshly prepared herbal teas in all three assays. However, significant increase (p< 0.05) of antioxidant activity was exhibited only in β-carotene linoleate bleaching assay for each probiotic herbal teas. The viability of lactic cultures in fermented herbal teas declined significantly (p< 0.05) with time and lost viability completely after 1 week of cold storage 4 °C. Generally, it can be concluded that 3 minutes of brewing is the best brewing time to yield more phenolic compounds from herbal teas. Moreover, the selected herbal teas are not the best but can considered to be average substrates for the cultivation of Lactobacillus casei. Furthermore, lactic fermentation also has a positive effect on the antioxidant activity of herbal teas and this can be implemented by the food industry to improve the nutritive value of food.